Chemical imaging of lignocellulosic biomass by CARS microscopy - Pohling, Christoph; Brackmann, Christian; Duarte, Alex; Buckup, Tiago; Enejder, Annika; Motzkus, Marcus (Journal of biophotonics, 2014)
Chemical and structural composition of wood biomass is studied by label-free and chemically specific Coherent Anti-Stokes Raman Scattering (CARS) microscopy. A concept developed for assignment and semi-quantitative imaging of sample components; cellulose, hemicellulose, and lignin; by multiplex CARS microspectroscopy and subsequent data analysis is presented. Specific imaging without fluorescence backround is achieved an order of magnitude faster compared with conventional Raman microscopy. Laser polarization control yield information on molecular arrangement in wood fibers. Narrowband CARS excitation of single vibrations allows for three-dimensional volume imaging. Thus, CARS microscopy has potential as an important instrument for characterization of lignocellulosic materials. (© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)
Online veröffentlicht: 9. Juli 2013
Gesehen am 02.09.2020